Phosphinecarboxamide as an unexpected phosphorus precursor in the chemical vapour deposition of zinc phosphide thin films. Issue 28 (26th June 2018) - Beddoe, Samuel V. F.; Cosham, Samuel D.; Kulak, Alexander N.; Jupp, Andrew R.; Goicoechea, Jose M.; Hyett, Geoffrey
Abstract : Phosphinecarboxamide and zinc acetate have been used to form thin films of zinc phosphide via aerosol assisted chemical vapour deposition. Abstract : This paper demonstrates the use of phosphinecarboxamide as a facile phosphorus precursor, which can be used alongside zinc acetate for the chemical vapour deposition (CVD) of adherent and crystalline zinc phosphide films. Thin films of Zn3 P2 have a number of potential applications and phosphinecarboxamide is a safer and more efficient precursor than the highly toxic, corrosive and flammable phosphine used in previous CVD syntheses.